2002
DOI: 10.1097/00000637-200201000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Difference of Molecular Response to Ischemia???Reperfusion of Rat Skeletal Muscle as a Function of Ischemic Time: Study of the Expression of p53, p21WAF-1, Bax Protein, and Apoptosis

Abstract: The authors investigated the expression of p53, p21(WAF-1), Bax protein, and apoptosis to elucidate the cellular response to ischemia-reperfusion of skeletal muscle using the rat lower limb model. The rat left lower limb was dissected in the inguinal region, isolating the bony femoral muscles, and the femoral vessels were clamped to produce an ischemic condition. After 3 or 6 hours, the clamps were removed and the gastrocnemius muscle was resected at various times up to 72 hours after reperfusion. Five specime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 22 publications
4
24
0
Order By: Relevance
“…It would be interesting to compare the present results to the findings obtained from complete ischemia. Although the experimental protocol of our study was not exactly the same from the study conducted by Hatoko and colleagues (14), our findings generally shared the similarities in the results that apoptotic signaling responded to 6 h of muscle ischemia. By clamping the femoral blood vessels, ischemic condition was produced in rat gastrocnemius muscle (14).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…It would be interesting to compare the present results to the findings obtained from complete ischemia. Although the experimental protocol of our study was not exactly the same from the study conducted by Hatoko and colleagues (14), our findings generally shared the similarities in the results that apoptotic signaling responded to 6 h of muscle ischemia. By clamping the femoral blood vessels, ischemic condition was produced in rat gastrocnemius muscle (14).…”
Section: Discussionsupporting
confidence: 86%
“…Although the experimental protocol of our study was not exactly the same from the study conducted by Hatoko and colleagues (14), our findings generally shared the similarities in the results that apoptotic signaling responded to 6 h of muscle ischemia. By clamping the femoral blood vessels, ischemic condition was produced in rat gastrocnemius muscle (14). They reported that the protein level of p53, p21 , and Bax, as determined by Western immunoblotting, was not changed immediately after 6 h of ischemia alone but was gradually increased during the subsequent 12-72 h of reperfusion (14).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In ischemia-reperfusion of skeletal muscle using the rat lower limb model, p53 also accumulated with concomitant increase in the level of Bax protein and apoptosis was induced (Hatoko et al 2002). Following 14 days of denervation, the extent of apoptotic DNA fragmentation was increased by 100 % in the gastrocnemius muscle.…”
Section: Discussionmentioning
confidence: 99%
“…By postulating that the pressure ulcer problem can be adequately described by the applied pressure, the duration of loading, tissue density, tissue modulus of elasticity, and tissue blood flow, it was predicted in a dimensional analysis that the allowable pressure p decreased with duration time t in the manner of p ∝ t -4/3 (87). The hypothesis involving blood flow occlusion was among the earliest hypotheses made to explain the formation of pressure ulcer (89 documented that tissues can survive ischemia for duration much longer than those usually observed in pressure ulcer formation (94).…”
Section: Hypotheses For the Formation Of Pressure Ulcermentioning
confidence: 99%